Role of acute exacerbations in skeletal muscle impairment in COPD. (2nd January 2021) - Gosker, Harry R.; Langen, Ramon C.; Simons, Sami O.
ABSTRACT: Introduction : Muscle impairments are prevalent in COPD and have adverse clinical implications in terms of physical performance capacity, disease burden, quality of life and even mortality. During acute exacerbations of COPD (AECOPDs) the respiratory symptoms worsen and this might also apply to the muscle impairments. Areas covered : This report includes a review of both clinical and pre-clinical peer-reviewed literature of the past 20 years found in PubMed providing a comprehensive view on the role of AECOPD in muscle dysfunction in COPD, the putative underlying mechanisms and the treatment perspectives. Expert opinion : The contribution of AECOPD and its recurrent nature to muscle impairment in COPD cannot be ignored and can be attributed to the acutely intensifying and converging disease-related drivers of muscle deterioration, in particular disuse, systemic inflammation and corticosteroid treatment. The search for novel treatment options should focus on the AECOPD-enhanced drivers of muscle dysfunction as well as on the underlying, mainly catabolic, mechanisms. Considering the impact of AECOPD on muscle function, and that of muscle impairment on the recurrence of exacerbations, counteracting muscle deterioration in AECOPD provides an unprecedented therapeutic opportunity.